Tanggung Jawab Penyanyi sebagai Penampil Karya terhadap Pencipta dalam Komersialisasi Lagu pada Konser Musik yang Diadakan oleh Pihak Ketiga Berdasarkan Undang-Undang Hak Cipta - Siti Nabila Salmaa; Muhamad Amirulloh; Tasya Safiranita (Lembaga Pengembangan Kinerja Dosen, 2025)
The commercialization of songs through music concerts organized by third parties is a form of commercial exploitation of works. However, this practice often harms creators because songs are used without the payment of royalties. The case of Agnez Mo against Ari Bias is a clear example of the neglect of copyright as the exclusive right of the creator, while singers only have a position through related rights. This study aims to analyze the legal status and relationship between creators and singers, including the responsibilities of singers in music concerts based on Law Number 28 of 2014 concerning Copyright. The methods used are normative and empirical legal methods, with data collection from primary, secondary, and tertiary legal materials, as well as interviews, which are then analyzed normatively and qualitatively. The results of the study show that the legal relationship between creators and singers is reciprocal, but creators have a higher position in accordance with the alter ego principle and personality theory. Singers, based on the principle of good faith, the theory of responsibility, and the principle of suum cuique tribuere, are obliged to respect the rights of creators.